LEGAL CERTAINTY OF THE IMPLEMENTATION OF FIXED-TIME EMPLOYMENT AGREEMENTS AFTER THE LABOR CREATION ACT OF 2023 - Widagdo, Gatot Subroto (Awang Long Law Review, 2025)
This study aims to analyze legal certainty in the implementation of Fixed-Term Employment Agreements (PKWT) following the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. This regulation brings significant changes to the provisions of PKWT, previously stipulated in Law Number 13 of 2003 concerning Manpower. Using a normative legal approach, this study examines the paradigm shift from a system that primarily protects workers to one that is more flexible and oriented toward business interests. The results indicate that although the Job Creation Law provides greater flexibility for employers and adds new forms of protection in the form of compensation and electronic registration, the elimination of contract time limits and the provision for automatic conversion of PKWT to PKWTT reduces legal certainty for workers. To achieve a balance between employer interests and the protection of workers' rights, strengthening derivative regulations, increasing labor oversight, and providing legal education for all parties is necessary to ensure that the implementation of PKWT is carried out in accordance with the principles of justice and legal certainty in Indonesia's rule of law.